Gestión del " Capabillity maturity model integration" (CMMI) Nivel 3 y de la norma ISO 25001 en la empresa Novacomp S.A. - Campos-Chavarria, Dolger Gerardo (Instituto Tecnológico de Costa Rica, 2017)
The following document will explain in detail the final report corresponding to the course of Professional Practice (IC8842) of the Computer Engineering Career at Instituto Tecnológico de Costa Rica, San Carlos Headquarters. This practice is being carried out in the company Novacomp S.A. in the project: Management of the “Capability Maturity Model Integration” (CMMI) level 3 and ISO 25001. There is a need identified during this process, to systematize the management of projects, enabling a model that enables, executes, and delivers tangible results in established time periods. This study parts from the best practices for project management to identify known methodologies for such, and wraps up with workflows, templates and tools that allow for the execution of continuous improvement projects. During the first stage of the project, the organization’s current situation and gap analysis was performed, measuring against the CMMI maturity model. In brief, it was determined an execution urgency derived in project’s documentation and planning misses. This reinforced negatively on process gaps, lack of objective estimations including risk assessments, failures in scope definition and quality assurance, among others. The proposed solution contains a new work structure, focused in efficiency and effectiveness. It includes a new workflow to initiate, plan, execute, monitor, control and close continuous improvement projects. It also relies on new custom templates and tools, being the minimum required documentation to complete the proposed activities.
Informe final de práctica de especialidad (Bachillerato en Ingeniería en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2017.
Keywords: Desarrollo de software - Evaluación; Desarrollo de Software - Mejoramiento continuo; Desarrollo de Software - Mantenimiento